KAJIAN TAKHRĪJ DAN ANALISIS SANAD–MATAN HADIS TENTANG MADU SEBAGAI OBAT PERSPEKTIF ILMU HADIS KONTEMPORER - Evi Naimah; M. Fatchurrohman; Ngatmin Abbas (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study examines the hadith on honey as medicine through the perspective of Hadith Studies (Ilmu Hadis), focusing on takhrīj, chain (sanad) analysis, and textual (matan) criticism. Although the hadith on honey is frequently discussed in the context of prophetic medicine, its analysis from a strict hadith methodological framework remains limited. This research aims to assess the authenticity of the hadith, analyze the narrators’ network, and explore its relevance within contemporary hadith discourse. Employing qualitative library research, primary data were obtained from canonical hadith collections, particularly Ṣaḥīḥ al-Bukhārī and Ṣaḥīḥ Muslim, while secondary data were drawn from works of jarḥ wa ta‘dīl, hadith commentaries, and recent academic journals. The findings reveal that the hadith is classified as ṣaḥīḥ li dhātih, with a continuous chain and reliable transmitters. The matn analysis confirms its coherence with Qur’anic principles and rational considerations. This study emphasizes the importance of grounding thematic hadith studies in rigorous hadith methodology.